new topics of constitutional rigidity - Sánchez Morales, Mauricio (Universidad Autónoma de Tamaulipas, 2019)
Constitutionalism has, as a key issue, that the States use the Constitution as the supreme norm of the entire legal order. Its evolution has moved from a liberal model to a democratic one, where being under a rigid constitution plays a role of utmost importance at the moment of trying to reform the content of the Social Pact. It is at that very moment, that I observe the existence of several models, at state level, where the aggravating factors vary to such a degree that it is feasible to rethink what should be understood by a rigid constitution in contemporary Mexico, and what elements should be included in attention to a democratic state like ours.